The Impact of Special Economic Zones (SEZs) on Economic Growth: Where the Absorption Capacity of Domestic Labor Stands? - Shujaa Waqar; Iftikhar Badshah; Marium Sara Minhas Bandeali; Saira Ahmed (Faculty of Economic and Business, 2021)
This study designs to assess and infer the effect of Special Economic Zones under China-Pakistan Economic Corridor on the economic growth of Pakistan through technological spillovers and the absorption capacity of domestic laborers. The present study develops a theoretical model and an empirical panel model to test whether the intervention of Special Economic Zones in the Asian developing countries has affected their economic growth through domestic Human Capital. For relevant results, we have employed the GMM model for the panel data set. The results indicate that the technological enhancement accumulates the economy through various other selected indicators rather than domestic labor productivity. The human capital remains inconsequent in this nexus. This condition gives us guidelines to follow pro-human capital policies to accumulate domestic human capital before the intervention from the foreign firms on our soil. Subsequently, much waited for dynamic or long-run benefits in terms of human capital can be attained rather than static effects.JEL Classification: C23, D24, J24How to Cite:Waqar, S., Badshah, I., Bandeali, M. S. M., & Ahmed, S. (2021). The Impact of Special Economic Zones (SEZs) on Economic Growth: Where the Absorption Capacity of Domestic Labor Stands?. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.19386.